Implementasi Model Pembelajaran Means Ends Analysis (MEA) pada Pembelajaran Matematika - Utomo, Budi; Sukarno, Sukarno; Prastiti, Tri Dyah (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to describe plans, implementation, constraints and solutions, as well as the results of implementing the MEA learning model on mixed arithmetic problem solving materials with integers. The research was conducted with a qualitative approach. Research data were collected through interviews, observation, and documentation studies. The data analysis technique uses descriptive analysis with the steps: data collection, data reduction, data display, verification and confirmation of conclusions (Conclusion Drawing and Verification). The results of the study concluded that teacher preparation carried out by teachers in implementing MEA learning was: (1) preparing lesson plans, (2) preparing learning materials according to core competencies, basic competencies and learning objectives, (3) preparing learning media according to the MEA learning model in the form of interactive powerpoints and learning materials to be studied, (4) developing learning strategies and steps, (5) compiling assessment instruments accompanied by answer sheets and assessment criteria. The stages of implementing the MEA model learning are: (1) preliminary activities, (2) core activities, (3) closing, and (4) assessment of learning outcomes. The internal obstacles to MEA learning are: (1) students' difficulties in completing and solving math problems, (2) students' lack of enjoyment in learning material, (3) students with low math mastery tend to be passive, (4) the process of compiling math problem solving questions requires thinking mature and long process, (5) difficulty expressing math problems to students. External constraints: (1) Limited time and space for interaction between teachers and students due to the COVID-19 pandemic so that learning is less effective, (2) patterns of learning mathematics that are abstract in nature that have not been supported by concrete learning media cause the completion of problem solving questions to be less understandable by learners.